Estilo de liderazgo de las docentes de educación inicial de las instituciones educativas del distrito Callao - Gamarra Vargas, Mary Trinidad (2010)
The following research is a simple descriptive cross-sectional study, aimed to identify the predominant leadership style used by preschool level teachers at educational institutions of Callao Region. In order to collect the data, it was used the leadership style questionnaire (CELID - A) of Morales - Molero, which reflects the typology presented by Bernard Bass, which considers three types of leadership styles. This test allows testers to get a score for each of the three styles and dimensions involved. The population sample considered 237 teachers, who belong to 34 educational institutions. After the study, the results showed that most of the preschool level teachers use the laissez faire and transactional style.